The Global Research Trends on Importance of Emotional Intelligent - Muhammad Fikri Fauzi (Journal of Education Counseling, 2025)
Emotional intelligence is a necessary skill to possess because with good emotional intelligence, individuals can manage themselves and maintain good interactions in the volatile and highly uncertain 21st century. This study aims to determine the development of research on aspects of emotional intelligence published from 2016 to 2025 through the Dimensions AI database and the help of the VOS Viewer application accessed on October 2, 2025. The PRISMA method or Preferred Reporting Items for Systematic Reviews and Meta-Analysis is the method used. The results of the study showed 780,078 articles with the keyword 'emotional intelligence', which then left 389 scientific articles that fit the research criteria. Ronnel Bornasal King from the Chinese University of Hong Kong, China is one of the active authors in this study while the journal Frontiers in Psychology, Switzerland is a journal listed as one of the journals actively publishing related articles.